Effects of Cognitive Behaviour Therapy (CBT) and Dance Movement Therapy (DMT) on Anhedonic Behaviour, among Schizophrenic Patients - Ogechi , Godsgift Christopher; Obi-Nwosu, Harry; Okechukwu , Christian Onuoha (International Journal of Health Sciences, 2024)
Purpose: This study aimed at assessing the therapeutic potency of cognitive behaviour therapy and dance movement therapy on anhedonic behaviour, among schizophrenic patients. Methodology: Thirty (30) in-patients were randomly selected from the in-patients that met the inclusion criteria for this study at Neuropsychiatric Hospital Nawfia. This study utilized a pretest posttest between subject design; while 18-item Temporal Experience of Pleasure Scale (TEPS) was used for data collection; and ANOVA statistic was adapted for data analysis at .01, and .05 levels of significance. Findings: From the purpose and objectives of this study, three hypotheses were proposed and tested. The result revealed that hypotheses 1 and 2 were accepted; indicating that significant differences were found between CBT, and Control, as well as between DMT and Control groups. Hence, the first and second hypothesis of the study were accepted. However, the third hypothesis of the study was rejected. Indicating that no significant difference was found between CBT and DMT. Unique Contributions to Theory, Policy and Practice: Theoretically, the finding in this present study validated the theoretical framework of this study. Hence, can be used for further elaboration of social cognitive theory. The researchers recommended dance movement therapy as one of the psychotherapeutic paradigm for the improvement of pleasure seeking behaviour among schizophrenic patients; since the research findings showed that it can contribute meaningfully towards the improvement of anhedonia associated with schizophrenia. The study has also shown that DMT is as effective as CBT in the reduction of anhedonia associated with schizophrenia so, DMT should be used in situations where CBT cannot be administered or as an alternative.